If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(9/10)-(1/3)=x
We simplify the equation to the form, which is simple to understand
(9/10)-(1/3)=x
Remove unnecessary parentheses
+ 0.9-( + 0.33333333333333)=x
Remove unnecessary parentheses
+ 0.9-0.33333333333333=x
We move all terms containing x to the left and all other terms to the right.
-1x=-0.9 + 0.33333333333333
We simplify left and right side of the equation.
-1x=-0.56666666666667
We divide both sides of the equation by -01 to get x.
x=0.56666666666667
| 5.972*2.71828=389.40563584 | | 7x-8(x+1)-3=3(x+4)-4(x+1) | | 3x+7=9x+3 | | 3n-5=-21 | | 33.33333=4+-1 | | c=0.75y+50 | | x+26=2x+4 | | 2x+y=110 | | (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 |